Dynamic Changes in Parameters of Complete Blood Count Predict Disease Severity and Prognosis in Patients with COVID-19; A Prospective Study - Toktam Alirezaei; Mahdi Baratnia; Rama Bozorgmehr; Yasamansadat Keshmiri; Faezeh Ebrahimpour; Maryam Arefnia; Mohammadali Ghodsirad (Novelty in Biomedicine)
Background: The pandemic of the coronavirus disease 2019 (COVID-19) is a major cause of death worldwide; thus, disease prediction is important. This study aimed to evaluate dynamic changes of complete blood count parameters in adult patients to predict disease severity.